An investigation of the significance of learned helplessness on membership participation in co-operative movements - Norman, Paul Deon (Rhodes University, Faculty of Humanities, Department of Psychology, 1991)
In this study the psychological phenomenon of learned helplessness is investigated to determine its significance as a characteristic of members of progressive co-operatives within the South African context. Most of the members of these co-operatives are black South Africans. It is argued that because of the country's racial policy, many of the members have become accustomed to a passive response to events in their lives and this gives rise to their failure to utilise the freedom and opportunities of the co-operative structure. The researcher hypothesises that this passive response could be explained in terms of a high level of learned helplessness among co-operative members. Two hypotheses are investigated in this study: Hypothesis 1: Passive co-operative members will have higher levels of learned helplessness than active members. Hypothesis 2:The level of learned helplessness decreases as the length of co-operative members involvement increases. Data collection for this study was carried out by combining a personal interview and a standardised questionnaire (the Attributional Style Questionnaire). To distinguish between the passive and active members, a Participation Index was constructed. The ASQ was translated into Xhosa, adapted for the sample and two translators were employed to conduct the interviews in Xhosa. The sample consisted of 50 black South Africans, many with limited education and was drawn from six co-operatives in the Eastern Cape. No significant differences were found between the active and passive groups in terms of their levels of learned helplessness. Furthermore, the length of involvement in the co-operative had no effect on the level of learned helplessness. No support was found therefore for Hypothesis l and 2. A significant difference, however, was found between active and passive members and the number of months of involvement. This suggests that the length of involvement has an effect on how active members will be in the co-operative. The results of this study indicate that generally the sample does not suffer from learned helplessness. It is argued that Hypothesis 2 is not supported due to confounding variables. The study raises many doubts as to the reliability of the ASQ and the Participation Index used in the study.
Keywords: Learned helplessness; Psychology; Black people -- South Africa; Attributional Style Questionnaire; Partician Index; Co-operatives; Helplessness (Psychology); Black people -- Psychology